Pendampingan Implementasi E-Arsip Untuk Proyek Infrastruktur Tol - Gustriansyah, Rendra; Suhandi, Nazori; Puspasari, Shinta; Sanmorino, Ahmad; Wiyanto, Ari (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
The conventional management of archives using physical files at the Jambi-Betung II Toll Road Land Procurement Commitment Making Officer (PPK-PPTJT) agency results in slow document retrieval, a higher risk of data loss, and limited accessibility to important information. This community service initiative aims to enhance the technological skills of human resources at PPK-PPTJT Jambi-Betung II, particularly in electronic archive management. The methods employed involve socialization and technical training on using e-archive applications for four PPK-PPTJT employees. Evaluation was conducted through questionnaires and interviews to assess the participants' improvement in understanding and skills. The results demonstrated a significant increase in participants' capabilities: 25% reported a better understanding of the benefits of e-archives, 75% enhanced their operational application skills, and 25% felt more confident in managing electronic archives. The implementation of e-archives has successfully reduced reliance on physical documents and expedited the toll road land procurement administration process, ultimately increasing the operational efficiency of PPK-PPTJT Jambi-Betung II.Keywords: e-archive; mentoring; land procurement; archive management  Abstrak: Pengelolaan arsip secara konvensional dengan menggunakan berkas fisik di instansi Pejabat Pembuat Komitmen Pelaksana Pengadaan Tanah Jalan Tol (PPK-PPTJT) Jambi-Betung II menyebabkan lambatnya pencarian dokumen, rentan kehilangan data, dan terbatasnya aksesibilitas terhadap informasi penting. Tujuan pengabdian ini adalah untuk meningkatkan kapasitas sumber daya manusia di PPK-PPTJT Jambi-Betung II dalam hal digitalisasi dan pengelolaan arsip elektronik. Metode yang digunakan meliputi sosialisasi, pelatihan teknis penggunaan aplikasi e-arsip bagi empat pegawai PPK-PPTJT. Evaluasi dilakukan dengan angket dan wawancara untuk mengukur peningkatan pemahaman dan keterampilan empat peserta. Hasil evaluasi menunjukkan peningkatan signifikan: 19% peserta lebih memahami manfaat e-arsip, 31% peningkatan kemampuan operasional aplikasi, dan 25% peningkatan kepercayaan diri dalam pengelolaan arsip elektronik. Penerapan e-arsip berhasil mengurangi ketergantungan pada arsip fisik, mempercepat proses administrasi pengadaan tanah jalan tol, efisiensi ruang penyimpan, dan kemudahan monitoring dan evaluasi proses operasional PPK-PPTJT Jambi-Betung II.Kata kunci: e-arsip; pendampingan; pengadaan tanah; pengelolaan arsip